Analisis Pengaruh Kepemimpinan TransformasionalDisiplin Kerja, Lingkungan Kerja Dan InovasiTerhadap Kinerja Karyawan Studi Di Goro Assalam Surakarta - Dela, Anggun Astria, Nur Achmad, S.E., M.Si (2015)
The purpose of this study was to analyze the influence of Transformational Leadership, Discipline Work, Work Environment, and Innovation to employee performance. The technique used in this study is a random sampling, so that the population in this study were employees of Goro Assalam Surakarta. The number of samples in this study were 97 employees. To achieve the objectives of the research, an analytical tool used in this research is the analysis of the validity, reliability, hypothesis testing, and classical assumption test performed using SPSS 20.00. From the results of the t test in this study showed that the factors of transformational leadership does not have a significant impact on employee performance to value (0,833 ≤ 1.662), the variable innovation gives the greatest influence with the value (6.182 ≥ 1.661), and other variables significantly influence employee performance. Based on F test showed that transformational leadership factor, work discipline, work environment, and innovation in partial or collectively have a significant impact on employee performance Goro Assalam Surakarta, with values ​​≥ (24.788 ≥ 2.47). Keywords: transformational leadership, work discipline, work environment, innovation management, performance.